Studies in chronic allergic bronchopulmonary aspergillosis. 2. Radiological findings. Issue 3 (June 1977) - Malo, J L; Pepys, J; Simon, G
Abstract : The characteristics and the incidence of changes in plain chest radiographs were analysed in detail in 50 asthmatic patients with chronic allergic bronchopulmonary aspergillosis in whom the diagnosis had been made from 2 to 25 years previously (mean duration 10-9 years). One thousand two hundred and forty-two chest radiographs, an average of about two per year per patient, were reviewed. Two hundred and sixty-seven acute episodes of transient shadows (a mean of 5-3 per patient), mostly homogeneous consolidations and band-like shadows, were recorded throughout the period of follow-up. Features of overinflation were present in 21 patients in the first radiograph and in 17 in the last, the decrease being attributed to the effects of permanent lung damage due to the allergic aspergillosis. Permanent changes, such as tubular and ring shadows, loss of vascular shadows, and lobar shrinkage were recorded in 41 patients at the start and in 49 at the end of the follow-up. The tubular shadows were found in 28 patients in the first radiograph and in 45 in the last, whereas ring shadows were seen in 18 and 30 patients respectively. Half of the episodes of consolidation and atelectasis left permanent changes, mainly ring shadows, as seen in the last radiograph. Of the band-like shadows, 32% were found to be followed by the subsequent appearance of tubular shadows. Statistically significant correlations were found between the duration of aspergillosis, the number of transient shadows throughout the period of follow-up, the extent of the permanent shadows, and the reduction of gas transfer factor at the time of the final follow-up.